Search for Meaning through Interfaith Dialogue - Thelle, Notto R. (Japanese religions, 1976)
Review of Doi, Masatoshi. Search for Meaning through Interfaith Dialogue. Publisher: Tokyo : Kyo Bun Kwan, 1976